Elephants (Loxodonta africana) of Zoba Gash Barka, Eritrea: Part 2. Numbers and distribution, ecology and behaviour, and fauna and flora in their ecosystem - Jeheskel Shoshani; Yohannes Hagos; Yohannes Yacob; Medhanie Ghebrehiwet; Emun Kebrom (Pachyderm)
This second article in Pachyderm focuses on the ecology and habitat utilization of elephants presently occupying the Gash Barka [Zoba Gash Barka] area of south western Ertirea based on field data collected during 2001-2003. (Shoshani et al., 2003) Animals of all ages were observed in the population of about 100 animals, which during the dry season occupy the Gash and Setit River valleys in Gash Barka region. These elephant migrate to northern Ethiopia during the dry season. Data suggests the elephant play a keystone role in the ecology of this area, and the authors note : 'It appears that a symbiotic relationship exists between elephants and doum palms and between elephants and baboons, and a commensal relationship may exist between elephants and helmeted guinea fowls'. The authors note: 'We started a new method using soleprints as a possible character for reliably identifying individual elephants.'